72-h therapeutic hypothermia improves neurological outcomes in paediatric asphyxial out-of-hospital cardiac arrest–An exploratory investigation. (December 2018) - Lin, Jainn-Jim; Lin, Chia-Ying; Hsia, Shao-Hsuan; Wang, Huei-Shyong; Chiang, Ming-Chou; Lin, Kuang-Lin; ,
Abstract: Background: Recent studies suggest that a 48-h therapeutic hypothermia protocol does not improve outcomes in paediatric out-of-hospital cardiac arrest survivors. The aim of this study was to evaluate the effect of 72-h therapeutic hypothermia at 33 °C compared to normothermia at 35.5 °C–37.5 °C on outcomes and the incidence of adverse events in paediatric asphyxial out-of-hospital cardiac arrest survivors. Methods: We conducted this retrospective cohort study at a tertiary paediatric intensive care unit between January 2010 and June 2017. All children from 1 month to 18 years of age with asphyxial out-of-hospital cardiac arrest and a history of at least 3 min of chest compressions who survived for 12 h or more after the return of circulation were eligible. Results: Sixty-four patients met the eligibility criteria for the study. Forty-nine (76.6%) of the 64 children were male, and the mean age was 4.86+/−5.26 years. Twenty-four (37.5%) of the children had underlying disorders. The overall 1-month survival rate was 43.2%. Twenty-five (39.1%) of the children received therapeutic hypothermia at 33 °C for 72 h. The 1-month survival rate was significantly higher ( p = 0.037) in the therapeutic hypothermia group (15/25, 60%) than in the normothermia group (12/39, 30.8%). The therapeutic hypothermia group had significantly better neurological outcomes (7/15, 46.7%) than the normothermia group (1/12, 8.3%) ( p = 0.043). Conclusion: Paediatric asphyxial out-of-hospital cardiac arrest was associated with high mortality and morbidity. Seventy-two-hour therapeutic hypothermia was associated with a better 1-month survival rate and 6-month neurological outcomes than normothermia in our paediatric patients with asphyxial out-of-hospital cardiac arrest.